PENGARUH PART WHOLE METHOD TERHADAP TEKNIK DASAR PASSING BAWAH BOLA VOLI - Trimizi, Trimizi; Supriatna, Eka; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe background of this research is underhand passing technique in volleyball of student of SMP Mandiri Pontianak which is not improved, seen from the results are still many students who are under standards of KKM’s value. Therefore, this research want to get more information about underhand passing technique in volleyball by using a Part Whole Method. The purpose of this research is to determine the effect of the Part Whole Method to underhand passing basic technique in volleyball for students of SMP Mandiri Pontianak. The research method used is the experimental method, with the use of Pre-experimental design approach with the One Group Pre-test Post-test design. The population of this research is grade VIII students of SMP Mandiri Pontianak, which amounted 15 students. And sample for this research are all learners. The data collector technique used is a test. The data collection tool used is a underhand passing technique test of volleyball. The results is the Part Whole Methode does affect to the underhand passing basic technique which is obtained tcount (6,806) > ttable (2,114) and the percentage value is 14,41%. Based of the results of the analysis it can be concluded there is a significant influence of Part whole Method against the underhand passing basic technique the volleyball of students SMP Mandiri Pontianak.Keywords: Part Whole Method, Underhand Passing, Volleyball